Estimating Staffing Needs in the Justice Sector - Gramckow, Heike (World Bank, Washington, DC, 2014)
Justice system agencies around the world continue to seek adequate methods to estimate staffing needs. Especially when caseload rise and budgets are limited, the pressure is on to justify adequate staffing with solid data. The simpler approaches of basing staffing needs on number of cases filed or population numbers have proven to be imprecise at best and seriously flawed at worst. The search for better estimation measures first led to weighted caseload studies, which weighed the complexity and other special needs of different case types. As these methods still did not provide an accurate assessment, efforts continue to be made to develop a more precise measure of not just caseload but workload, a measure that factors in the time spent on managing the case and on the increasing amount of non-case-related work, such as administration, training, outreach, travel, etc. This paper describes the leading approaches (including the analytical, Delphi, and weighted caseload methods) used throughout the world for determining workload among justice sector employees, presenting the benefits and limitations of each. The paper then focuses on what is currently viewed as the more optimum method of the weighted workload study, and offers a step-by-step outline of how this kind of study can be developed and implemented. Also considered are the dual challenges of forecasting future staffing needs and incorporating performance measures to promote quality decision making and cost-efficient court procedures and services.